Hemocyte Responses of the Oyster Crassostrea hongkongensis Exposed to Diel-Cycling Hypoxia and Salinity Change - Xie, Zhe; Wei, Shuaishuai; Dong, Haomiao; Chen, Hui; Zhang, Qianqian; Liu, Wei; Peng, Jinxia; Sokolova, Inna M.; Hu, Menghong; Wang, Youji (Frontiers in Marine Science, 2021)
Marine hypoxia caused by nutrient enrichment in coastal waters has become a global problem for decades, especially diel-cycling hypoxia that occurs frequently in the summer season. On the contrary, sudden rainstorms, and freshwater discharge make salinity in estuarine and coastal ecosystems variable, which often occurs with hypoxia. We found mass mortality of the Hong Kong oyster Crassostrea hongkongensis in the field where hypoxia and salinity fluctuation co-occur in the summer season during the past several years. To investigate the effects of diel-cycling hypoxia and salinity changes on the hemocyte immune function of C. hongkongensis, oysters were exposed to a combined effect of two dissolved oxygen (DO) concentrations (24 h normal oxygen 6 mg/L, 12 h normal oxygen 6 mg/L, and 12 h hypoxia 2 mg/L) and three salinities (10, 25, and 35‰) for 14 days. Subsequently, all treatments were restored to constant normal oxygen (6 mg/L) and salinity under 25‰ for 3 days to study the recovery of hemocyte immune function from the combined stress. Hemocyte parameters were analyzed by flow cytometry, including hemocyte mortality (HM), total hemocyte count (THC), phagocytosis (PHA), esterase (EST) activity, reactive oxygen species (ROS), lysosomal content (LYSO), and mitochondrial number (MN). The experimental results showed that diel-cycling hypoxia and salinity changes have obvious interactive effects on various immune parameters. In detail, diel-cycling hypoxia and decreases in salinity led to increased HM, and low salinity caused heavier impacts. In addition, low salinity, and diel-cycling hypoxia also led to decreases in LYSO, EST, and THC, while the decrease of PHA only occurs in the early stage. On the contrary, ROS production increased significantly under low salinity and hypoxic conditions. After 3-day recovery, THC, PHA, EST, LYSO, and MN were basically restored to normal, while HM and ROS were still significantly affected by diel-cycling hypoxia and salinity change, indicating that the combined stress of diel-cycling hypoxia and salinity changes had latent effects on the immune function of C. hongkongensis. Our results highlight that diel-cycling hypoxia and salinity change may impair the health and survival of the Hong Kong oyster C. hongkongensis and may be the key factors for the mass mortality of this oyster in the field.